Unsteady thermal convection of a heat-generating liquid having variable viscosity in a vertical cooling cylinder Available to Purchase; International Journal of Numerical Methods for Heat & Fluid Flow; Vol. 35, iss. 11 - Kudrov A. I. Alexander Ivanovich (2025, 2025)
Title screen